The Translation of Japanese Manga Meitantei Conan: The Similarities and Differences between The Original Japanese Version and the Indonesian Translated Version - Idrus Idrus (Universitas Diponegoro, 2021)
Japanese comics or manga have caught the world’s attention in recent years. It conveys stories through words and images in a specific order resulting in beautiful works. Now, manga is translated into various languages in the world, including Indonesian. The following study entailed a comparative analysis of the manga Meitantei Conan into Indonesia, primarily concentrating on: the format, for example, the arrangement of pages, lettering, and typography, what was translated what was not. In translating Japanese manga into Indonesian, it was found that there were similarities (retained elements) and differences (adjusted elements). We can found similarities between the original Japanese version and the Indonesian translated version of manga in the writing composition on the chapter title and onomatopoeia. Besides, there are also similarities in cultural terms because the translator maintains terms in Japanese as a translation strategy. The main difference between Original Japanese comics and the Indonesian translated version is the binding system of using, the type of font, and the use of Indonesian cultural elements so that the dialogue of the story characters is more communicative and easy to understand.